The pediatric surgeon's perspective on the liver hanging maneuver: a case report and literature review - Gigola, Francesca; Bici, Kejd; Morabito, Antonino; Grimaldi, Chiara (Frontiers in Pediatrics, 2025)
IntroductionThe liver hanging maneuver (HM) is a well–established technique in hepatic surgery, primarily employed to optimize exposure and simplify parenchymal transection during liver resections. While its efficacy and safety have been extensively documented in adult populations, reports on its application in pediatric surgery are limited. This may be related to peculiarities of the liver anatomy and texture in children and to some specific issues of pediatric liver tumors, especially hepatoblastoma (HB).MethodsThis study reviews the technical adaptations, feasibility, and outcomes of the HM in children, focusing on its role in both routine liver resections and complex cases, such as the separation of conjoined twins. Data of patients treated with and without HM at our center were retrospectively analyzed and a review of recent literature on this topic was performed.ResultsA total of 16 pediatric patients (7 females) underwent HM during hepatic resections with a median age at surgery of 16 months (IQR: 8–22.5). No complications or mortality related to surgery were observed.DiscussionResults demonstrate that with appropriate modifications, the HM is a safe and effective technique in children, offering advantages in minimizing bleeding while improving surgical efficiency.